2018
DOI: 10.17219/acem/75499
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sitagliptin, inhibitor of dipeptidyl peptidase-4 (DPP-4), on the ADMA-DDAH-NO pathway in ischemic and reperfused rat livers

Abstract: Background. A correlation between the level of asymmetric dimethylarginine (ADMA)-the inhibitor of the nitric oxide (NO) synthesis-and the liver function and survival after a liver transplantation has been reported. Objectives. The aim of this study was to evaluate the effect of sitagliptin-the inhibitor of dipeptidyl peptidase-4 (DPP-4)-on the NO-ADMA-dimethylarginine dimethylaminohydrolase (DDAH) pathway in rat livers subjected to ischemia/reperfusion (IR). Material and methods. The rats received sitagliptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…In vivo and in vitro experiments have demonstrated that the ddaH1/adMa/no signaling pathway is closely associated with cardiovascular disease (10,12), cancer (13,36), liver diseases (37), preeclampsia (38,39) and ischemic and reperfusion injury (40). The present study demonstrated that TAC-induced a significant increase in ADMA concentration and a decrease in ddaH1 expression and no production, which were ameliorated by Bae treatment.…”
Section: Discussionsupporting
confidence: 55%
“…In vivo and in vitro experiments have demonstrated that the ddaH1/adMa/no signaling pathway is closely associated with cardiovascular disease (10,12), cancer (13,36), liver diseases (37), preeclampsia (38,39) and ischemic and reperfusion injury (40). The present study demonstrated that TAC-induced a significant increase in ADMA concentration and a decrease in ddaH1 expression and no production, which were ameliorated by Bae treatment.…”
Section: Discussionsupporting
confidence: 55%
“…Recently, a large body of evidence has accumulated showing sitagliptin effectiveness in lessening tissue damage during intestinal [ 24 , 32 ], cardiac [ 23 , 33 ], cerebral [ 30 ], testicular [ 31 ] and renal [ 28 , 29 ] ischemia-reperfusion insult. Likewise, sitagliptin has reduced the histopathological signs of injury and decreased the serum activities of ALT and AST in animal models of hepatic IR [ 21 , 22 , 25 , 26 ], acting via mechanisms employing its anti-inflammatory and antioxidative properties. Accordingly, an alleviation of oxidative stress in the ischemic liver has previously been shown, manifested by upregulated activity and/or the expression of enzymatic antioxidants, including paraoxonase-1 [ 22 ], superoxide dismutase (SOD) [ 22 , 25 ] and heme oxygenase [ 25 ], which has been accompanied by an increased concentration of reduced glutathione [ 25 ] and a diminished level of lipid peroxidation [ 22 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is partly in line with our previous observations regarding the effect of this drug on selected parameters of the NO-ADMA-DDAH pathway. The 14-day treatment with sitagliptin resulted in an increase in the L-arginine/ADMA ratio in the non-ischemic group and an increase in the activity of dimethylarginine dimethylaminohydrolase (DDAH) in the ischemic group [ 21 ]. The l -Arginine/ADMA ratio reflects l -arginine bioavailability for NOS, while DDAH is an enzyme metabolizing ADMA, the main NOS inhibitor [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations